Growth of Spirulina platensis Cultured with Inorganic Fertilizer (Urea, TSP and ZA) and Chicken Manure - Utomo, N.B.P; Winarti, .; Erlina, A. (Jurnal Akuakultur Indonesia, 2005)
This experiment was conducted to compare the effectiveness of inorganic fertilizer and chicken manure on population growth and nutrient content of Spirulina platensis. It was found that Spirulina platensis cultured in inorganic medium reached a maximum population on day-9 with a density of 614.77x103 Sin/ml, containing 56.39% of crude protein and 17.92% of lipid. On the other hand, Spirulina platensis cultured in 250 ppm of chicken manure reached a maximum population on day-4 with a density of 434.32x103 Sin/ml, containing 45.39% of crude protein and 12.50% of lipid. Keywords: spirulina, Spirulina platensis, culture, inorganic fertilizer, chicken manure, population maximum   ABSTRAK Penelitian ini dilakukan untuk membandingkan efektivitas pupuk inorganik (urea, TSP dan ZA) dan kotoran ayam terhadap pertumbuhan dan kandungan nutrien Spirulina platensis.  Hasil penelitian menunjukkan bahwa Spirulina platensis dikultur menggunakan pupuk inorganik mencapai puncak populasi pada hari ke-9 dengan kepadatan 614,77x103 Sin/ml, mengandungkan protein kasar 56,39% dan lemak 17,92%. Sementara itu, Spirulina platensis dikultur menggunakan kotoran ayam 250 ppm mencapai puncak populasi pada hari ke-4 dengan kepadatan 434,32x103 Sin/ml, kandungan protein kasar 45,39% dan lemak 12,50%. Kata kunci: spirulina, Spirulina platensis, kultur, pupuk inorganik, kotoran ayam, populasi maksimal